Monoclonal antibodies identify two neutralization-sensitive epitopes in Besnoitia besnoiti endocytes - Njagi, O.N.; Entzeroth, R.; Nyaga, P.N.; Musoke, A.J. (Springer, 2004)
Four monoclonal antibodies were produced against endozoite membrane and cytoplasmic antigens of B. besnoiti. In immunofluorescence antibody tests, three of the clones, designated 2M3C5, 2M1G8 and 2M9G3 recognized antigens restricted to the anterior pole of the endozoites. The fourth clone, 2M9C4, recognized a membrane-associated component in a beaded pattern, cytoplasmic granules and extracellular background. The staining characteristics differed from the solid diffuse staining of polyclonal serum. On Western blots of detergent-soluble extracts fractionated under non-reducing conditions in 10% SDS-PAGE gels, mAbs 2M3C5, 2M1G8 and 2M9G3 recognized a common antigen at >200 kDa. Recognition with mAb 2M3C5 was consistently different in intensity and extent. Monoclonal antibody 2M9C4 recognized a single antigen at 75 kDa. The antibodies significantly reduced infectivity of Besnoitia endozoites into cultured cells, demonstrating the potential role of the antigens in the invasion process and raising the possibility of development of a vaccine and diagnostic tests for the disease.